Перспективы развития рынка балкерного тоннажа - Тостоган, В.Г. (Економічні інновації, 2009)
Розглядається стан ринку масових вантажів з 2003 по 2008 роки. Дано економічну оцінку факторам, що сприяли значному підвищенню фрахтових ставок у 2007-2008 роках диференційовано за основними дедвейт ними групами суден та основними напрямками перевезень. Проаналізовано попит та пропозицію тоннажу. Зроблено висновки відносно перспектив розвитку ринку перевезень масових вантажів. Article presents condition of bulk cargo market from 2003 to 2008. An economic evaluation is given to the factors which was instrumental in the considerable increase of shipping’s rates in 2007-2008 years deadweight is differentiated after basic by them by the groups of ships and basic directions of transportations. Demand and supply of tonnage is analyzed. Conclusions are done in relation to the prospects of market of transportations of mass loads development.